2021
DOI: 10.1177/11206721211039350
|View full text |Cite
|
Sign up to set email alerts
|

Effect of light backscattering from anterior segment structures on automated flare meter measurements

Abstract: Background: To evaluate effect of maximal anterior cortical lens density, iris scatter and anterior chamber depth on laser flare photometry. Methods: Patients diagnosed with clinical uveitis were enrolled in the study. Clinical flare gradings were recorded upon the Standardization of Uveitis Nomenclature. Aqueous flare was measured with an automated device (Kowa FM-700). Back-scattering from anterior cortical lens and anterior iris surface was calculated from Scheimpflug images. A curvilinear regression model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…26 However, the properties of the cataract may falsely change the flare due to increased background light journals.sagepub.com/home/oed TherapeuTic advances in Ophthalmology scatter. 131 Cataract surgery technique influences postoperative flare and can be minimized with small incisions, efficient phacoemulsification and in-the-bag IOL placement. The majority of IOLs used today do not affect flare differently from one another.…”
Section: Discussionmentioning
confidence: 99%
“…26 However, the properties of the cataract may falsely change the flare due to increased background light journals.sagepub.com/home/oed TherapeuTic advances in Ophthalmology scatter. 131 Cataract surgery technique influences postoperative flare and can be minimized with small incisions, efficient phacoemulsification and in-the-bag IOL placement. The majority of IOLs used today do not affect flare differently from one another.…”
Section: Discussionmentioning
confidence: 99%
“…Повідомляється про зв'язок значень ЛФ зі щільністю передньої кортикальної зони кришталика [18]. Водночас думка про вплив розсіювання світла помутнінням у кришталику на значення ЛФ залишається дискусійним [19,20].…”
Section: лазерна фотометрія в здорових осібunclassified
“…It is well known that backscatter form cataractous lenses has a considerable effect over LFP measurements,[ 20 ] although it has been shown that milder light backscatter from a noncataractous anterior cortical lens could also have an additional effect over LFP readings. [ 21 ] Iris scatter is also a contributing factor, which could be decreased by mydriasis[ 1 ] or proper positioning of the calculation window during LFP acquisition, for the amount of scattering is inversely proportional with the distance to the scattering surface. [ 22 ]…”
Section: F Actors That Affect Lfp Measur...mentioning
confidence: 99%